Functionality of Elaeocarpus serratus leaves on growth, meat quality and cost return analysis in broiler rearing (Asian Journal of Medical and Biological Research, 2021)
The study was conducted to evaluate the effects of olive leaves with probiotics (OLP) on growth performance, carcass characteristics, meat quality, blood parameters and oxidative stability of meat in broiler. A total of 160 day old, unsexed Cobb-500 chicks were distributed in to five dietary treatment groups: Control (Basal diet), OLP-1 (Basal diet + 0.4% OLP, DM basis), OLP-2 (Basal diet + 0.8% OLP, DM basis), OLP-3 (Basal diet + 1.2% OLP, DM basis) and OLP-4 (Basal diet + 1.6% OLP, DM basis) having 4 replications with 8 birds in each in a completely randomized design. Results showed that the live weight, overall average daily gain (ADG) increased significantly (p